A practice of user profile in big data - Xiaoxia WANG; Jingsha LIU; Dandan XU (Dianxin kexue)
The development of telecom market focused on the development model from the incremental development model.In the case of incremental development model,it has become a consensus to prevent customer reduction,to extend customers’ life cycle,to enhance revenues and earnings .User profile technology was used to defend telecom business and customer base in the face of pressure from OTT.Big data technology of user profile was used to describe customer demand,match customer and product,so as to make a breakthrough in marketing.